2014
DOI: 10.3389/fnbeh.2014.00322
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Psychotropic Agents on Extinction of Lever-Press Avoidance in a Rat Model of Anxiety Vulnerability

Abstract: Avoidance and its perseveration represent key features of anxiety disorders. Both pharmacological and behavioral approaches (i.e., anxiolytics and extinction therapy) have been utilized to modulate avoidance behavior in patients. However, the outcome has not always been desirable. Part of the reason is attributed to the diverse neuropathology of anxiety disorders. Here, we investigated the effect of psychotropic drugs that target various monoamine systems on extinction of avoidance behavior using lever-press a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 83 publications
2
5
0
Order By: Relevance
“…A stronger factor is temperament, represented by the inbred WKY rat, which shows robust patterns of avoidance responding. With regard to acquisition with a 60-s WS, several patterns noted previously were evident here (although not stressed in the results section): (1) WKY rats lacked warm-up, as acquisition progressed WKY rats avoided on the first trial of a session, whereas SD rats generally exhibited an escape response (Servatius et al, 2008 ), (2) WKY rats exhibited slower rates of extinction (Servatius et al, 2008 ; Jiao et al, 2014 ). In stark contrast to SD rats, WKY rats acquired with a 10-s WS with females WKY rats expressing avoidance to a higher degree than male WKY rats.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…A stronger factor is temperament, represented by the inbred WKY rat, which shows robust patterns of avoidance responding. With regard to acquisition with a 60-s WS, several patterns noted previously were evident here (although not stressed in the results section): (1) WKY rats lacked warm-up, as acquisition progressed WKY rats avoided on the first trial of a session, whereas SD rats generally exhibited an escape response (Servatius et al, 2008 ), (2) WKY rats exhibited slower rates of extinction (Servatius et al, 2008 ; Jiao et al, 2014 ). In stark contrast to SD rats, WKY rats acquired with a 10-s WS with females WKY rats expressing avoidance to a higher degree than male WKY rats.…”
Section: Discussionsupporting
confidence: 67%
“…As an arbitrary response, rates of nonspecific responding are generally low enhancing sensitivity (Servatius et al, 2008 ; Avcu et al, 2014 ). An escape response is generally acquired early in training with avoidance emerging and reaching asymptotic performance over several sessions of training (Servatius et al, 2008 ; Jiao et al, 2011 , 2014 ; Pang et al, 2011 ; Avcu et al, 2014 ; Beck et al, 2014 ). Although avoidance is not expressed as quickly as other preparations (e.g., shuttle box), the slowness in acquisition is cited as a virtue (Bolles, 1970 ).…”
Section: Introductionmentioning
confidence: 99%
“…In session 4, mice treated with 20 and 40 mg/kg showed shorter response latencies than controls. These results, which suggest an enhancement in acquisition of avoidance learning within some bupropion groups, confirm those of previous studies with this drug that indicated an improvement of other learning tasks, such as retrieval of inhibitory avoidance (Barros et al, 2002), lever-press avoidance active task (Jiao et al, 2014), conditioned place preference (Ortmann, 1985), conditioned emotional response (Lipina and Roder, 2010;Carmack et al, 2014), or novel object recognition (Kruk-Słomka et al, 2014). Moreover, present data agree with previous observations showing that bupropion reverses reserpineinduced impairment in a conditioned avoidance task (Nakagawa et al, 1997) and reverses nicotine withdrawal-associated deficits in contextual fear conditioning by enhancing retrieval processes (Portugal and Gould, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…Given that previous data on the behavioural effects of bupropion in active avoidance tasks are limited (Jiao et al, 2014), we consider that present results add new information about the ability of bupropion to induce beneficial changes in the control of emotional responses. Considering that the active avoidance task is a relatively complex form of learning in which the animals have to learn a particular behavior in order to avoid the application of a stressor as a footshock, the performance displayed by animals treated with bupropion during sessions (jointly with the increase in the number of avoidances and the decrease in response latency observed here) suggests that this drug may improve the control of emotional responses.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation